Enhancement of protein production by microalgae Dunaliella salina under mixotrophic conditions using response surface methodology1. Issue 48 (28th May 2015) - Kadkhodaei, S.; Abbasiliasi, S.; Shun, T. J.; Fard Masoumi, H. R.; Mohamed, M. S.; Movahedi, A.; Rahim, R.; Ariff, A. B.
<x xml:space="preserve">Abstract</x> Schematic diagram of the upstream and downstream factors affecting transgene expression.